Program Pembinaan Narapidana di Lembaga Pemasyarakatan Kelas IIA Banceuy dalam Upaya Pemenuhan Hak-Hak Narapidana - Dimas Agung Widodo; Dey Ravena (Bandung Conference Series: Law Studies, 2024)
Abstract. This research focuses on the development of prisoners in order to fulfill the rights of prisoners in the Class IIA Banceuy Penitentiary. The aim of this research is to determine the fulfillment of prisoners' rights in the class IIA Banceuy penitentiary and the factors that hinder and support the fulfillment of prisoners' rights in the class IIA Banceuy penitentiary. This research approach method is qualitative with a type of non-doctrinal legal research. Descriptive research specifications with interview data collection and literature study. This research shows that the fulfillment of the rights of convicts at the Class IIA Banceuy Penitentiary while serving their criminal period has been ongoing and in accordance with what is contained in the legislation. The inhibiting factors in fulfilling prisoners' rights are the lack of motivation of prisoners to take part in coaching activities and excessive or over capacity housing. Abstrak. Penelitian ini berfokus kepada pembinaan narapidana dalam rangka memenuhi hak-hak narapidana di Lembaga Pemasyarakatan kelas IIA Banceuy. Tujuan penelitian ini untuk mengetahui pemenuhan hak narapidana di lembaga pemasyarakatan kelas IIA Banceuy dan faktor-faktor yang menghambat dan mendukung. Metode pendekatan penelitian ini kualitatif dengan jenis penelitian hukum non doktrinal. Penelitian ini menunjukkan bahwa pemenuhan hak-hak Narapidana di Lembaga Pemasyarakatan Kelas IIA Banceuy selama menjalani masa pidana telah berjalan dan sesuai dengan apa yang terdapat dalam perundang-undangan. Faktor penghambat dalam pemenuhan hak narapidana ialah kurangnya motivasi narapidana untuk mengikuti kegiatan pembinaan dan kapasitas hunian yang berlebihan atau over kapasitas.